SMART DOOR LOCK SYSTEM DEVELOPMENT PROTOTYPE USING RFID TECHNOLOGY ID-12 - Siti Aisyah; Yusmar Ali; Komda Saharja; Suhendra Suhendra; Asrul Sani (Kresnamedia Publisher, 2022)
This innovative door lock system is designed to make it easier to control security in certain homes or rooms. This system can also be used in government offices and factories to restrict someone from entering a room that just anyone can not enter. In this system, the automatic door lock uses an ID-12 type RFID reader, Tag/Transponder, Arduino UNO R3, 5v Buzzer, Drop Bolt Lock, Relay Module, and LCD. The RFID reader ID-12 is used as a receiver, and the tag/transponder as a transmitter. This system works when the scanned RFID tag/card/transponder sends hexadecimal data to the RFID Reader ID-12, which then, from the RFID Reader, will receive and send data to the Arduino. Then the Arduino UNO will process it by reading the program module (data from the RFID tag/card/transponder) and giving commands to the buzzer to make a sound or notification. The relay module is a connector or breaker for the deadbolt lock or solenoid to open and lock the door and a 16x2 LCD to display the status of the scanned RFID card. On standby, the LCD displays the words